Partisipasi Aktif Indonesia di RFMO: Langkah Taktis dalam Akselerasi Modernisasi Pengelolaan Perikanan - Jaya, Indra (Policy Brief Pertanian, Kelautan, dan Biosains Tropika, 2024)
Indonesian fisheries management is still faced with various challenges to ensure its sustainability. For example, widespread IUU fishing, weak enforcement of fisheries regulations, inadequate monitoring and supervision capabilities, and compliance with fisheries laws, remain major problems, hampering fisheries management efforts. In this Policy Brief, 3 (three) recommendations are presented in the context of modernizing Indonesian fisheries management through Indonesia's active participation in the RFMO, namely: (1) To have political commitment at the highest level of government to ensure active participation in the RFMO; (2) To invest in building institutional capacity to effectively engage in RFMO activities; and (3) To allocate adequate financial, human and technical resources to support active participation in RFMO activities. RFMOs have made significant contributions to fisheries management over the years, so that Indonesia can learn from the fisheries management practices that have been developed and implemented by RFMOs. By adopting best practices from RFMO, Indonesia can accelerate the modernization of its fisheries management to increase the effectiveness of management efforts and ensure the sustainability of fisheries.